Pertanggungjawaban Pidana Penyalahgunaan Wewenang yang Dilakukan oleh Pejabat Pembuat Komitmen dalam Pengadaan Barang/Jasa Pemerintah - Pramudya, Tika Roesvita; Sudarti, Elly; Liyus, Herry (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to identify and analyze the forms of abuse of authority committed by Commitment-Making Officials (PPK) in government procurement of goods and services, as well as their criminal liability for corruption offenses. This research employs a normative juridical method using statutory, conceptual, and case approaches. The results show that government procurement is one of the sectors most vulnerable to corruption. Abuse of authority by PPK may occur during project planning, procurement system selection, tender processes, the exercise of official authority, and budget management and disbursement. Common forms of misconduct include pre-arranged project allocations to certain vendors before budget approval, document manipulation, improper preparation of the Owner’s Estimate (HPS), price mark-ups, bribery, manipulation of tender winner selection, and falsification of bidding and project handover documents. Regarding criminal liability, a PPK may be held criminally responsible when their actions cause losses to state finances. Criminal responsibility is based on the existence of an unlawful act (*actus reus*) and a guilty mind (*mens rea*), whether committed intentionally or through negligence. Therefore, abuse of authority that results in financial losses to the state may serve as a basis for criminal prosecution under anti-corruption laws.